The Effects of Modeling Contingencies in the Treatment of Food Selectivity in Children With Autism. (November 2015) - Fu, Sherrene B.; Penrod, Becky; Fernand, Jonathan K.; Whelan, Colleen M.; Griffith, Kristin; Medved, Shannon
The current study investigated the effectiveness of stating and modeling contingencies in increasing food consumption for two children with food selectivity. Results suggested that stating and modeling a differential reinforcement (DR) contingency for food consumption was effective in increasing consumption of two target foods for one child, and stating and modeling a DR plus nonremoval of the spoon contingency was effective in increasing consumption of the remaining food for the first child and all target foods for the second child.